Book Review of “The Dysregulated Adult: Integrated Treatment Approaches” - Farley, Ned (Canadian Journal of Counselling and Psychotherapy, 2012)
This is a review of the newly published book, The Dysregulated Adult: Integrated Treatment Approaches, by Georgia A. DeGangi. The review summarizes the general purpose and content of the book, offers readers a more in-depth discussion of the content covered, and finally discusses this reviewer’s perception of how well the author was able to succeed in addressing the topic.